Social Media and SMEs: Benefits, Challenges, and Strategies - Martio, Mona (My University, 2024)
Social media has emerged as a powerful marketing and business tool. For small and medium- sized enterprises (SMEs), there are diverse possibilities in adopting and utilizing social media. This thesis discusses the benefits and challenges of social media for SMEs, as well as social media strategies, critical success factors (CSFs) and key performance indicators (KPIs). The findings indicate a strong connection between social media use and SME performance, as it positively impacts factors such as entrepreneurial orientation, as well as brand awareness and loyalty. SMEs face challenges because of their lack of resources and the uncontrollability of social media. To successfully utilize social media, SMEs must have a clearly defined strategy, based on which they can determine relevant CSFs and KPIs.

Sosiaalisesta mediasta on tullut tehokas markkinoinnin ja liiketoiminnan työkalu. Pienillä ja keskisuurilla yrityksillä (pk-yritykset) on monipuolisesti mahdollisuudeksia sosiaalisen median käyttöönotossa ja hyödyntämisessä. Tässä kandidaatintutkielmassa käsitellään sosiaalisen median etuja ja haasteita pk-yrityksille sekä sosiaalisen median strategioita, kriittisiä menestystekijöitä (CSF:t) ja KPI-mittareita. Tulokset osoittavat vahvan yhteyden sosiaalisen median käytön ja pk-yritysten suorituskyvyn välillä, sillä se vaikuttaa positiivisesti esimerkiksi yrittäjyyssuuntautuneisuuteen sekä bränditietoisuuteen ja -uskoisuuteen. Toisaalta pk-yritykset kohtaavat haasteita erityisesti resurssien puutteen ja sosiaalisen median hallitsemattomuuden vuoksi. Hyödyntääkseen sosiaalista mediaa menestyksekkäästi pk-yrityksillä on oltava selkeästi määritelty strategia, jonka pohjalta ne voivat määrittää asiaankuuluvat CSF:t ja KPI-mittarit.
Keywords: social media, entrepreneurship, entrepreneurial orientation, social CRM, social media CSFs, social media KPIs